The socio economic of development induced displacement: case of Porta farm - Chikumbu, Martin Tinashe (Midlands Sate University, 2015)
This research put its focus on the effects of development induced displacement. It however narrowed down the research to the socio-economic effects that arise due to Development Induced Displacement (DID). Of note is that the document was mainly focusing on involuntary displacement. The research took a case study of Porta Farm. Porta farm is a council owned farm that is just about 20km south of the Harare CBD. Porta Farm was created to be a temporary holding for the people who were taken from various parts of the town in a bid to clean the city in preparation for the coming of the Queen to the Congress of Head of States in the early 1990s. People were taken mainly from Mbare in Tagarira Flats and some came from Epworth. Thu study also then revealed that some people also came from Chirambuhuyo in Chitungwiza in preparation for another development. Some of the people were also taken from around town as they were the homeless and streets vagabonds. The population however grew as it was uncontrolled and the City Council was also not completing its task of moving all the people to their final respective places like Dzivarasekwa Extension. Some of the people were taken to neighboring farms and some were moved as far as Churu Farm which is in the opposite direction of the town, about 25km. The remainder are however now facing forced eviction again as they are now deemed illegal settlers. Worse is the fact that the City Of Harare now has plans of expanding and extending the Morton and Jeffrey water works plant at the very place. The people are therefore again forced to leave to pave way for this development. All these displacements however have effects which this study did take a closer and magnified look unto.